Consensus docking aid to model the activity of an inhibitor of DNA methyltransferase 1 inspired by de novo design - Prado-Romero, Diana L.; Gómez-García, Alejandro; Cedillo-González, Raziel; Villegas-Quintero, Hassan; Avellaneda-Tamayo, Juan F.; López-López, Edgar; Saldívar-González, Fernanda I.; Chávez-Hernández, Ana L.; Medina-Franco, José L. (Frontiers in Drug Discovery, 2023)
The structure-activity relationships data available in public databases of inhibitors of DNA methyltransferases (DNMTs), families of epigenetic targets, plus the structural information of DNMT1, enables the development of a robust structure-based drug design strategy to study, at the molecular level, the activity of DNMTs inhibitors. In this study, we discuss a consensus molecular docking strategy to aid in explaining the activity of small molecules tested as inhibitors of DNMT1. The consensus docking approach, which was based on three validated docking algorithms of different designs, had an overall good agreement with the experimental enzymatic inhibition assays reported in the literature. The docking protocol was used to explain, at the molecular level, the activity profile of a novel DNMT1 inhibitor with a distinct chemical scaffold whose identification was inspired by de novo design and complemented with similarity searching.